Cellular Pre-Adaptation to the High O2 Concentration Used in Standard Cell Culture Confers Resistance to Subsequent H2O2-Induced Cell Death - Jack B. Jordan; Miranda J. Smallwood; Gary R. Smerdon; Paul G. Winyard (MDPI AG, 2024)
The addition of hydrogen peroxide (H2O2) to cultured cells is widely used as a method to modulate redox-regulated cellular pathways, including the induction of programmed cell death in cell culture experiments and the testing of pro- and antioxidant compounds. Here, we assessed the effect on the cellular response to H2O2 of pre-adapting squamous cell carcinoma cells (A431) to the standard cell culture oxygenation of 18.6% O2, compared to cells pre-adapted to a physiological skin O2 concentration (3.0% O2). We showed that cells pre-adapted to 18.6% O2 resisted H2O2-induced cell death compared to cells pre-adapted to 3.0% O2 for 96 h prior to treatment with H2O2. Moreover, the enzymatic activities of catalase and glutathione reductase, as well as the protein expression levels of catalase, were higher in cells pre-adapted to 18.6% O2 compared to cells pre-adapted to 3.0% O2. H2O2-resistant cells, pre-adapted to 18.6% O2, exhibited increased nuclear Nrf-2 levels. It is concluded that A431 cells pre-adapted to standard cell culture oxygenation conditions resist H2O2-induced cell death. This effect may be related to their heightened activation of Nrf-2.